Should paediatric central lines be aspirated before use?. Issue 6 (26th October 2006) - Coulthard, Malcolm G; Skinner, Roderick
Abstract : As blood clots commonly occur in the lumens of paediatric haemodialysis central-venous lines, they must be routinely aspirated before use to prevent pulmonary emboli. The smaller diameter lines used for parenteral nutrition and cancer chemotherapy are seldom managed this way. We looked for clots formed when children undergoing cancer chemotherapy had their heparin-locked central lines accessed, and compared with the lines of children undergoing haemodialysis. Patients undergoing haemodialysis had clots aspirated on 83% of occasions, and each child had clots at least once. Clots also occurred in the smaller lines, but they were less frequent (64%, p = 0.01), and had a lower median weight than those in dialysis lines (14.1 v 25.2 mg, p = 0.01). When small diameter central lines are used without initial aspiration, small pulmonary emboli are likely to occur, but are unlikely to be individually clinically important. Daily use, as with long-term parenteral nutrition, might result in >3 g of clot being embolised annually. Consideration should be given to aspirating all paediatric central lines before use.